P-Wave Duration in Lead aVR and the Risk of Atrial Fibrillation in Hypertension - Francia, Pietro; Ricotta, Agnese; Balla, Cristina; Adduci, Carmen; Semprini, Lorenzo; Frattari, Alessandra; Modestino, Anna; Mercanti, Federico; Sensini, Isabella; Caprinozzi, Massimo; Tocci, Giuliano; Volpe, Massimo (Annals of noninvasive electrocardiology, 2015)
Background Hypertension entails atrial remodeling that affect P‐wave (PW) duration on electrocardiogram (ECG). PW indices (e.g., variance, dispersion, and terminal force) are associated with a higher risk for atrial fibrillation (AF), but their calculation requires multiple measurements of PW duration, limiting their use in clinical practice. We evaluated whether PW duration in specific ECG leads may identify patients with increased susceptibility to AF in a population of hypertensive patients. Methods In a case–control study, AF and control subjects were matched for age, sex, and left atrial (LA) dimensions. PW duration was measured from digitally stored ECGs. Logistic regression was used to assess the association of PW duration and indices with AF. Results We enrolled 44 hypertensive AF patients (16 paroxysmal and 28 persistent) and 44 hypertensive controls. AF and control subjects were matched for sex (males, n = 27), age (67 ± 8 years), LA diameter (40 ± 5 mm), and were comparable for left ventricular mass (45 ± 11 g/m2.7 vs 48 ± 12 g/m2.7, P = 0.19), ejection fraction (58 ± 7% in both groups), and prevalence of mild valvular heart disease (7% vs 5%; P = 0.64). PW duration in lead aVR was significantly higher in AF patients as compared with controls (115 ± 18 ms vs 101 ± 14 ms; P < 0.0001) and was the best independent predictor of AF in multivariable logistic regression (PW ≥ 100 ms: RR = 3.7; 95% CI: 1.3–10.3; P = 0.02). Conclusions Simple measurement of PW duration in lead aVR allows effective identification of AF patients in a population of hypertensives. Confirmation of this finding in a larger population would provide a simple and effective risk marker of AF in hypertensive patients.